Concurrent characterization of through-thickness permeability and compaction of fiber reinforcements. (February 2021) - Kabachi, M.A; Stettler, L.; Arreguin, S.; Ermanni, P.
Abstract: Flow-induced fiber-bed compaction has considerable effects on through-thickness permeability due to resulting changes in fiber-volume-fractions. This study introduces a novel method for the simultaneous characterization of compaction and unsaturated out-of-plane permeability of engineering textiles in one single experiment. The measurement technique relies on visually tracking flow-front positions and compaction during through-thickness impregnation using a camera and a rigid tool equipped with a pressure sensor and a transparent window. This strategy allows flow-induced fiber-bed compaction to be considered in unsaturated permeability measurements, providing permeability at different fiber-volume-fractions, whilst also providing dry and wet compaction curves. This new measurement tool also readily verifies any race-tracking that may occur during impregnation, which drastically influences flow behavior. The method is successfully validated through testing of glass fiber NCF and woven fabrics, where permeability results are compared to analytical solutions, while compaction results are compared to those obtained from a universal testing machine.